2018
DOI: 10.2308/accr-52197
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Internal Control and Financial Statement Audits: Are Two Audits Better than One?

Abstract: The quality of financial statement (FS) audits integrated with audits of internal controls over financial reporting (ICFR) depends upon the quality of ICFR information used in, and its integration into, FS audits. Recent research and PCAOB inspections find auditors underreport existing ICFR weaknesses and perform insufficient testing to address identified risks, suggesting integrated audits—in which substantial ICFR testing is required—may result in lower FS audit quality than FS-only audits. We compare a 2007… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(26 citation statements)
references
References 62 publications
(84 reference statements)
2
22
0
Order By: Relevance
“…This study contributes to the body of knowledge, particularly where the findings show that internal control, internal audit, communication channels, compliance, and risk assessment are good determinants of accounting quality. These factors further agree with those proposed by Bhaskar et al (2019). Our findings suggested that these should be strictly enforced, and accounting methods should be closely monitored.…”
Section: Discussionsupporting
confidence: 90%
“…This study contributes to the body of knowledge, particularly where the findings show that internal control, internal audit, communication channels, compliance, and risk assessment are good determinants of accounting quality. These factors further agree with those proposed by Bhaskar et al (2019). Our findings suggested that these should be strictly enforced, and accounting methods should be closely monitored.…”
Section: Discussionsupporting
confidence: 90%
“…Studies in the research streams of auditing and external reporting, for instance, are largely influenced by researchers from the United States. Here, the common agreement concerning the definition of internal control appears to be internal Kanagaretnam et al 2010;Huang et al 2009;Naiker and Sharma 2009;Wolfe et al 2009;Krishnan 2005) Balance between internal control and audit effort and pricing (Bhaskar et al 2019;Lee 2018;Ji et al 2018;Knechel et al 2009;Hunton et al 2008;Hoitash et al 2008; Pae and Yoo 2001) Importance of auditing for internal control (Oussii and Taktak 2018;Schroeder and Shepardson 2016;Haislip et al 2016;Holm and Laursen 2007;Jensen and Payne 2003) 1 3…”
Section: The Meaning Of Internal Controlmentioning
confidence: 99%
“…Third, we consider material weaknesses in internal control over financial reporting as a proxy of audit quality. Since the reporting of a material weakness is not necessarily revealing of audit quality in its own right, we first run a prediction model for the likelihood of reporting a material weakness and then compare whether the actual internal control opinion agrees with the predicted internal control opinion (Ge, Koester, and McVay 2017;Bhaskar, Schroeder, and Shepardson 2019). This measure provides a better estimate of the quality of audit services; for example, we can assess whether the auditor requires disclosure of a material weakness in settings in which a material weakness is more likely to occur.…”
Section: Audit Quality Dimensionsmentioning
confidence: 99%